2021
DOI: 10.7759/cureus.16831
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Fibrin Glue as an Ideal Treatment for the Pilonidal Disease

Abstract: Pilonidal sinus is an acquired condition caused by irritation to the hair follicles at the natal cleft, presenting with an abscess or chronic infection. It is prevalent in young adults affecting their productive lifestyle with morbidities. There are varieties of treatment options; however, there is no consensus yet for the ideal procedure. Less invasive procedures have evolved to replace the traditional surgical techniques, which cannot significantly reduce the risks of recurrence and wound complications despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…SiLaT is one of the promising techniques of the growing trend toward minimally invasive treatment of SPND, but it needs to be further investigated and validated, which is the main aim of the current study. The demographic characteristics of the patients were similar to those reported in the literature [1,2,[4][5][6]10,12,13].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…SiLaT is one of the promising techniques of the growing trend toward minimally invasive treatment of SPND, but it needs to be further investigated and validated, which is the main aim of the current study. The demographic characteristics of the patients were similar to those reported in the literature [1,2,[4][5][6]10,12,13].…”
Section: Discussionsupporting
confidence: 73%
“…The worldwide recurrence rate of surgical management of SPND is varied and reported in some studies to be as lower as 0.2%, with the best result achieved using modified Limberg flap [ 2 , 3 ]. Albabtain et al [ 15 ] and Almajid et al [ 16 ] reported a recurrence rate of 22.8% and 7.2%, respectively, for patients treated by surgical excision of SPND in the Kingdom of Saudi Arabia, while Abdelnaby et al [ 5 ] reported zero recurrence rate of sinus lay open technique in Egypt [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In more recent times, there has been a shift towards less invasive approaches aimed at balancing over/under treatment. These minimally invasive procedures include EPSiT, 11 Gips procedure, 12 sinusectomy, 13 Sinus Laser‐Assisted Closure (SiLaC), 14 and the use of products such as phenol 15 and fibrin glue 16 . These techniques remain in their infancy demonstrating a limited evidence base.…”
Section: Introductionmentioning
confidence: 99%